The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.7589/0090-3558-39.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus Antibody Occurrence in Bank Voles (Clethrionomys Glareolus) During a Vole Population Cycle

Abstract: Puumala virus, genus Hantavirus, is the etiologic agent of nephropathia epidemica, a mild form of hemorrhagic fever with renal syndrome. The bank vole (Clethrionomys glareolus) is the natural reservoir species of this hantavirus. We initiated sampling of bank voles at sites of recently identified human nephropathia epidemica cases and paired control sites in the fall of 1995 in coastal areas of northern Sweden. Sites were trapped annually in spring and fall until 1999. Prevalence of antibody to Puumala virus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 31 publications
(17 reference statements)
2
35
0
Order By: Relevance
“…In Finland and northern Scandinavia, bank vole populations show multiannual cyclic patterns of 3-4 years with increase, peak, and decline/low phase , Olsson et al 2003a, Hö rnfeldt 2004, Korpimä ki et al 2005. In Sweden, for example, bank vole abundance alone explained >70% of the variation in seasonal HFRS incidence (Olsson et al 2009), and in Finland the current increase or peak phase of the bank vole cycle was a good predictor of risk (Kallio et al 2009).…”
Section: Regional and Temporal Host Population Dynamicsmentioning
confidence: 94%
“…In Finland and northern Scandinavia, bank vole populations show multiannual cyclic patterns of 3-4 years with increase, peak, and decline/low phase , Olsson et al 2003a, Hö rnfeldt 2004, Korpimä ki et al 2005. In Sweden, for example, bank vole abundance alone explained >70% of the variation in seasonal HFRS incidence (Olsson et al 2009), and in Finland the current increase or peak phase of the bank vole cycle was a good predictor of risk (Kallio et al 2009).…”
Section: Regional and Temporal Host Population Dynamicsmentioning
confidence: 94%
“…A recent study found a negative correlation between density and prevalence in El Moro Canyon virus in western harvest mice . In bank voles, Puumala virus seroprevalence was well predicted in part by the phase of population, being highest after the peak, implying both density-dependence and delayed densitydependence (Olsson et al, 2002(Olsson et al, , 2003. (Boone et al, 1998) a + indicates a significant positive relationship, − a significant negative relationship, and 0 the lack of a significant relationship…”
Section: Introductionmentioning
confidence: 92%
“…Typical symptoms are fever, headache, muscle pain, nausea and impaired renal function [7,8]. The main reservoirs of PUUV are bank voles (Myodes glareolus), which can carry the infection persistently [9][10][11][12]. In Western and Central Europe the bank vole's preferred habitat is broad-leaved oak and beech forests as well as densely mixed forests with abundant herb and undergrowth layers [13].…”
Section: Introductionmentioning
confidence: 99%